Multiple regions within 8q24 independently affect risk for prostate cancer. - Haiman, C; Patterson, N; Freedman, M; Myers, S; Pike, M; Waliszewska, A; Neubauer, J; Tandon, A; Schirmer, C; McDonald, G; Greenway, S; Stram, DO; et al. (2007)
After the recent discovery that common genetic variation in 8q24 influences inherited risk of prostate cancer, we genotyped 2,973 SNPs in up to 7,518 men with and without prostate cancer from five populations. We identified seven risk variants, five of them previously undescribed, spanning 430 kb and each independently predicting risk for prostate cancer (P = 7.9 x 10(-19) for the strongest association, and P < 1.5 x 10(-4) for five of the variants, after controlling for each of the others). The variants define common genotypes that span a more than fivefold range of susceptibility to cancer in some populations. None of the prostate cancer risk variants aligns to a known gene or alters the coding sequence of an encoded protein.